Self-optimization energy management considering stochastic influences for a hybrid energy storage of an electric road vehicle - Romaus, Christoph; Wimmelbücker, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Contradictions and the Foundation of Logic in German Idealism - Ficara, Elena (La question de la logique dans l’Idéalisme allemande)

Kant e il rapporto dello scetticismo con la filosofia - Ficara, Elena (Akten des XI. Kant Kongresses)

Hegel Within Contemporary Logic - Ficara, Elena (Teoria)

Dialectic and Dialetheism - Ficara, Elena (History and Philosophy of Logic)

Wirkungsgradoptimale Arbeitspunktsteuerung für einen permanenterregten Synchronmotor mit vergrabenen Magneten unter Berücksichtigung von Temperatureinflüssen - Wallscheid, Oliver; Böcker, Joachim (ETG-Fachbericht-Internationaler ETG-Kongress 2013–Energieversorgung auf dem Weg nach 2050)

Discrete-time model of an IPMSM based on variational integrators - Specht, Andreas; Ober-Blöbaum, Sina; Wallscheid, Oliver; Romaus, Christoph; Böcker, Joachim (Electric Machines & Drives Conference (IEMDC), 2013 IEEE International)

The Berlin Group and the Philosophy of Logical Empiricism
Rezensionen: Zbl. Math. 1275.03016 (Leon Harkleroad)

Practice budgets and the patient mix of physicians-Evaluating the effects of remuneration system reforms on physician behaviour in Germany - Schmitz, Hendrik (Journal of Health Economics)

What accounts for the regional differences in the utilisation of hospitals in Germany? - Augurzky, Boris; Kopetsch, Thomas; Schmitz, Hendrik (The European Journal of Health Economics)

Health and the double burden of full-time work and informal care provision—Evidence from administrative data - Schmitz, Hendrik; Stroka, Magdalena A (Labour Economics)

Two-Phase Interleaving Configuration of the LLC Resonant Converter - Analysis and Experimental Evaluation - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Integrated Magnetic for DCM-PSFB Converter - Njiende, Hugues; Li, Rongyuan; Schafmeister, Frank; Ide, Peter

Resonant capacitor clamping circuit in resonant converter - Figge, Heiko; Schafmeister, Frank

Hybrid Energy Storage System (HES) - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)

Design of a high performance ferrite magnet-assisted synchronous reluctance motor for an electric vehicle - Paradkar, Milind; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Fast online model predictive control of IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Co-simulation of an electric traction drive - Schulte, Christoph; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Low Latency Hybrid Hardware-in-the-Loop Simulator for Railway Traction System - Tong, Laisheng; Zou, Huanqing; Sun, Meng; Böcker, Joachim (2013 IEEE Vehicle Power and Propulsion Conference (VPPC))

A Novel LC Resonant Based Partial Booster Scheme for Improved Efficiency and Reduced Cost of Transformerless Photovoltaic Inverters - Krishna, D.V.M.M.; Preckwinkel, H.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)